Leucine supplementation decreases HDAC4 expression and nuclear localization in skeletal muscle fiber of rats submitted to hindlimb immobilization - Alves, Paula; Cruz, André; Silva, William J.; Labeit, Siegfried; Moriscot, Anselmo S. (Cells, 2020)
In this study we surveyed a rat skeletal muscle RNA-Seq for genes that are induced by hindlimb immobilization and, in turn, become attenuated by leucine supplementation. This approach, in search of leucine-atrophy protection mediating genes, identified histone deacetylase 4 (HDAC4) as highly responsive to both hindlimb immobilization and leucine supplementation. We then examined the impact of leucine on HDAC4 expression, tissue localization, and target genes. A total of 76 male Wistar rats (~280 g) were submitted to hindlimb immobilization and/or leucine supplementation for 3, 7 and 12 days. These animals were euthanized, and soleus muscle was removed for further analysis. RNA-Seq analysis of hindlimb immobilized rats indicated a sharp induction (log2 = 3.4) of HDAC4 expression which was attenuated by leucine supplementation (~50%). Real-time PCR and protein expression analysis by Western blot confirmed increased HDAC4 mRNA after 7 days of hindlimb immobilization and mitigation of induction by leucine supplementation. Regarding the HDAC4 localization, the proportion of positive nuclei was higher in the immobilized group and decreased after leucine supplementation. Also, we found a marked decrease of myogenin and MAFbx-atrogin-1 mRNA levels upon leucine supplementation, while CAMKII and DACH2 mRNA levels were increased by leucine supplementation. Our data suggest that HDAC4 inhibition might be involved in the anti-atrophic effects of leucine.